The Structure of Asset Prices and Socially Useless/Useful Information - OHLSON, JAMES A. (Journal of Finance, 1984)
ABSTRACT This paper relates the value of additional information to asset prices in a pure exchange setting. The price structure of interest revolves around a “pricing‐hypothesis”: the prices in an economy with less information are unbiased estimators of the prices that would obtain in a more informative economy. Two basic results are developed. First, if the incremental information is useless then the pricing‐hypothesis applies. Second, if the pricing hypothesis is assumed valid, then the information is valuable in a weak sense. The results are also considered in the context of empirical research. The case is made for viewing statistical tests of association between prices and signals as tests of the social value of information.